High gain chopper supplied from PV system to fed synchronous reluctance motor drive for pumping water application - Z. M. Salem Elbarbary; Khalid Mehmood Cheema; Saad F. Al-Gahtani; Ragab A. El-Sehiemy (Scientific Reports, 2022)
Abstract Power generation for renewable energy sources increased rapidly during last few years. Similarly, the high gain dc–dc boost choppers are taking place of conventional power converters used for photovoltaic (PV) appliances. Researchers are developing different methods in order to provide high voltage gain, low ripple, reduced switch stress, low converter costs, and minimized variations of PV operating points. This study proposes a two-stage converter for a freestanding water pumping motor drive power by solar PV system. According to the proposed system, at first, a high gain (HG) cell and a DC-to-DC boost converter are combined to increase the PV voltage to high levels. Later on, the resulting dc voltage feds a three-phase synchronous reluctance motor drive that operates centrifugal pump load. The perturb and observe approach is utilized to get the maximum power out of the solar PV module. Moreover, indirect field-oriented control is implemented to accomplish smooth starting of synchronous reluctance motor. In order to validate the effectiveness of proposed technique, a MATLAB/Simulink environment-based simulation setup along with an experimental prototype is developed. Additionally, various cases are considered based on different operating conditions and irradiance levels to collect and analyse the results.